AGE AND ISOTOPIC GEOCHEMICAL CHARACTERISTICS OF ARCHEAN CARBONATITES AND ALKALINE ROCKS OF THE BALTIC SHIELD - Zozulya D.R.; Bayanova T.B.; Serov P.A. (My University, 2007)
Occurrences of Archean alkaline rocks are insignificant. Only a few complexes in the Canadian Shield (Superior Province), Greenland, Australia (Yilgarn Block), and South Africa are known to date. They are composed of alkali and nepheline syenites, foidolites, carbonatites, peralkaline granites, lamprophyres, and potassic volcanic rocks. The age of the oldest alkaline rocks is estimated at ~2.7 Ga. The Neoproterozoic and Phanerozoic alkaline rocks occur in three main geodynamic settings: (1) continental rifts, (2) oceanic islands, and (3) subduction zones (peralkaline granites in back-arc zones). The Early Precambrian alkaline rocks formed at hotspots of the oceanic crust and are unknown in continental rifts. Therefore, the geodynamic setting of the Archean alkaline rocks is interpreted as a subduction-related environment and the depleted mantle is thought to be their source. The Late Archean subduction-related alkaline complexes presumably formed at the final stages of the evolution of greenstone belts, while the depleted source is accounted for by the absence of metasomatic processes in the Archean mantle.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей